FACING CRIMINALITY ON FACEBOOK - Ekwok, Lawrence (PEOPLE: International Journal of Social Sciences, 2017)
This paper is titled: “Facing Criminality on Facebook”. Facebook as a social media technology-based interactive platform has no doubt raised the bar of interaction and communication among individuals, businesses, corporate organizations, and even governments and their agencies. This is especially so as it allows people and groups to create and share user-generated content such as individual profiles, texts, photos, audios and videos on a common connectivity. The platform has thus helped a great number of people and groups across the world to get information, inspiration, friends, do business, share ideas, pictures, audios and videos and even games faster than ever before. The fact that more than 1.65 billion people are active users of the Facebook platform emphasizes its relevance and impact in people’s lives globally, even as it stands out as the most popular social media or social network platform worldwide going by the number of users. But despite its relevance, impact and popularity, Facebook as a social networking site which was conceived primarily to enhance communication, promote friendship and businesses is fast becoming a platform for criminality and this has manifested variously in different parts of the world. This paper which is based on research conducted in three major cities in Nigeria – Calabar, Abuja and Lagos, shows that crimes such as scam, fraud, impersonation, hacking of accounts are fast becoming rampant on the social media platform, a situation which calls for urgent global attention and collaboration in combating these crimes.